USING OF GAMING TECHNOLOGIES IN PROFESSIONAL LINGVODIDACTIC EDUCATION OF FUTURE EDUCATOR OF PRESCHOOL EDUCATIONAL INSTITUTIONS - Rudenko, Yulia (Educological discourse, 2019)
The article raises the problem of the use of gaming technologies in professional lingvodidactic education of future educators of pre-school educational institutions, in particular, the essence of interactive learning is considered, the basic principles of using the latest, interactive, interactive-gaming, game technologies in the professional-speech activity of future educators are defined, the classification of gaming technologies is given (business games, educational games, gaming situations, discussions, trainings, language games, speech games, etc.), pedagogical requirements about the use of gaming technology in the educational process of higher education are substantiated, gaming technology features discussed in professional lingvodidactic education of future teachers. The essence of scientific concepts "gaming technologies", "language game technologies", "language game" is determined. The expediency of using gaming technologies in the professional linguistic and pedagogical education of future educators of pre-school institutions is described. Gaming technologies are defined in the study as a component of methodical support for the formation of professional and methodological orientation of future educators of pre-school institutions, creating a professional-oriented background, psychological comfort of the educational process; productive, developmental, creative solutions to tasks that promote the development of students’ creativity; interactive forms of learning that: are dynamic, create conditions for overcoming the psychological barrier in the system of "teacher-student", "student-student", contribute to the creation of a psychological comfort, emancipation of students; increase motivation / self-motivation of future educators for educational activities; is an effective learning management tool; provide for the reorientation of the educational process from the strictly regulated, passive-reproductive to the subject-subject activity; contribute to the formation and development of personal professional qualities of future educators (creativity, emotionality, creativity, imaginative thinking, non-standard, etc.); рrovide educational activities on a positive emotional background with the optimal combination of reproductive, productive, innovative creative activities of participants in the educational process; contribute to the formation of reflection / self-reflection skills, control / self-control, correction / self-correction of the assimilation of educational information. The prospect of further scientific research of the initiated research is seen in the development of a system of gaming technologies, trainings for speech development of future educators of pre-school education institutions.